The Syntactic Figure of "Repetition" In Iqbal Mirza's Idiostyle - Ubaydulloyevna, Zulaypoyeva (Innovative Technologica: Methodical Research Journal, 2025)
This article analyzes the syntactic figure “repeat” in the work of Iqbal Mirzo, a bright representative of Uzbek poetry, as an important sign of his idiostyle. In the poems of Iqbal Mirzo, repetitions are manifested not only as an artistic method, but also as a means of expressing the poet's own unique worldview, feelings and thoughts. The article outlines the role of repetition in the style of the poet, the influence of his poems on musicality, rhythmic structure and emotionality through examples. This study serves a deeper understanding of the linguistic and stylistic features of Iqbal Mirzo's poetry.